Abdominal pain in a young girl. Issue 844 (February 1996) - Handa, R.; Chirukpalli, R.; Agarwal, S.; Mukhopadhyaya, S.; Gupta, R.; Sood, R.; Meena, H. S.; Wali, J. P.
Abstract : A 14-year-old girl was admitted to our hospital with peri-umbilical pain associated with obstipation and vomiting. Plain erect X-rays of the abdomen revealed multiple air fluid levels. A supine X-ray is shown in this figure.